Nanotechnology-Based Drug Delivery Strategies to Repair the Mitochondrial Function in Neuroinflammatory and Neurodegenerative Diseases - Luis F. González; Lorenzo E. Bevilacqua; Rodrigo Naves (MDPI AG, 2021)
Mitochondria are vital organelles in eukaryotic cells that control diverse physiological processes related to energy production, calcium homeostasis, the generation of reactive oxygen species, and cell death. Several studies have demonstrated that structural and functional mitochondrial disturbances are involved in the development of different neuroinflammatory (NI) and neurodegenerative (ND) diseases (NI&NDDs) such as multiple sclerosis, Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis. Remarkably, counteracting mitochondrial impairment by genetic or pharmacologic treatment ameliorates neurodegeneration and clinical disability in animal models of these diseases. Therefore, the development of nanosystems enabling the sustained and selective delivery of mitochondria-targeted drugs is a novel and effective strategy to tackle NI&NDDs. In this review, we outline the impact of mitochondrial dysfunction associated with unbalanced mitochondrial dynamics, altered mitophagy, oxidative stress, energy deficit, and proteinopathies in NI&NDDs. In addition, we review different strategies for selective mitochondria-specific ligand targeting and discuss novel nanomaterials, nanozymes, and drug-loaded nanosystems developed to repair mitochondrial function and their therapeutic benefits protecting against oxidative stress, restoring cell energy production, preventing cell death, inhibiting protein aggregates, and improving motor and cognitive disability in cellular and animal models of different NI&NDDs.